Perovskite solar cell and preparation method thereof

By introducing polyvinyl acetate and other modifiers into the perovskite film preparation process, the reaction between lead iodide and organic ammonium salt is regulated, and the problem of lead iodide residue in perovskite film is solved, improving the crystallinity of the film and the performance of the battery.

CN119894218APending Publication Date: 2025-04-25JINGPENG ENERGY (SHENZHEN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510219006.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the two-step preparation process of perovskite film, insufficient reaction between organic ammonium salt and lead iodide lead to a large amount of residual lead iodide, affecting battery efficiency and stability.

Method used

The first modifier polyvinyl acetate is introduced into the lead iodide layer, and combined with the second modifier such as potassium chloride or perfluorooctyrene quaternary amine iodide, the reaction between lead iodide and organic ammonium salt is delayed, and the nucleation and crystallization process of the perovskite film is optimized by regulating the reaction conditions and ratio.

Benefits of technology

The residue of lead iodide in perovskite films is significantly reduced, the crystallinity and low defect state density of the film are improved, thereby improving the photoelectric conversion efficiency and stability of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894218A_ABST
    Figure CN119894218A_ABST
Patent Text Reader

Abstract

The invention discloses a perovskite solar cell and a preparation method, and relates to the technical field of perovskite solar cells. The perovskite solar cell provided by the invention comprises a perovskite light absorption layer, wherein the perovskite light absorption layer comprises a first modifier; the first modifier comprises polyvinyl acetate. According to the technical scheme, a two-step preparation process of the perovskite solar cell and the corresponding perovskite thin film is designed, the first modifier polyvinyl acetate is introduced into the lead iodide layer, so that the reaction between lead iodide and FAI and MACl in the organic ammonium salt layer is delayed, and the reaction is slower and milder; therefore, the nucleation and crystallization processes of the perovskite thin film are optimized, and the prepared perovskite solar cell has higher photoelectric conversion efficiency and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite solar cells, and in particular to a perovskite solar cell and a preparation method thereof. Background Art

[0002] As a new generation of thin-film solar cells, perovskite solar cells have become the most promising emerging photovoltaic technology for commercial applications due to their high photoelectric conversion efficiency, low preparation cost and scalability. The two-step preparation process for perovskite films currently under development is to first deposit a layer of lead iodide, and then deposit an organic ammonium salt to react with lead iodide to finally form perovskite; compared with the one-step method, the prepared film has high density and is easy to prepare large-area perovskite films. However, the perovskite film prepared by the two-step method also has typical technical problems, such as insufficient reaction between organic ammonium salt and lead iodide, resulting in a large amount of lead iodide residue, which makes the perovskite film have poor crystallinity and high defect state density, thus affecting the battery efficiency and battery stability. Summary of the invention

[0003] The main purpose of the present invention is to develop a two-step preparation process for a perovskite solar cell and a corresponding perovskite film, so that the perovskite film has less lead iodide residue, higher crystallinity and lower defect state density, so that the prepared solar cell has higher cell efficiency and cell stability.

[0004] To achieve the above object, the present invention provides a perovskite solar cell, wherein the perovskite solar cell comprises a perovskite light absorbing layer, wherein the perovskite light absorbing layer comprises a first modifier; and the first modifier comprises polyvinyl acetate.

[0005] In one embodiment, the weight average molecular weight of the polyvinyl acetate is 20,000 to 100,000.

[0006] In one embodiment, the perovskite light absorbing layer further includes a metal halide, and the metal halide includes lead iodide.

[0007] In one embodiment, the perovskite light absorbing layer further comprises an organic ammonium salt, and the organic ammonium salt comprises FAI and MACl.

[0008] In one embodiment, the perovskite light absorbing layer further includes a second modifier; the second modifier includes at least one of potassium chloride and perfluorooctyl quaternary ammonium iodide.

[0009] The present invention also provides a method for preparing the perovskite solar cell, which comprises the following steps:

[0010] S1, forming a conductive substrate and an electron transport layer in sequence;

[0011] S2, dissolving a metal halide and a first modifier in a solvent to obtain a metal halide precursor solution; depositing the metal halide precursor solution on the surface of the electron transport layer obtained in step S1, and annealing to form a metal halide layer;

[0012] S3, dissolving an organic ammonium salt in a solvent to obtain an organic ammonium salt solution; depositing the organic ammonium salt solution on the surface of the metal halide layer obtained in step S2, and annealing to form a perovskite light-absorbing layer;

[0013] S4, forming a hole transport layer and a metal back electrode in sequence on the surface of the perovskite light-absorbing layer obtained in step S3 to obtain the perovskite solar cell.

[0014] In one embodiment, in the step S1, the electron transport layer is prepared from a SnO2 solution, and the mass fraction of SnO2 particles in the SnO2 solution is 3 wt%.

[0015] In one embodiment, in the step S2, the amount of the first modifier in the metal halide precursor solution is 0.1 mg / mL to 1 mg / mL.

[0016] In one embodiment, in the step S2, the amount of the metal halide in the metal halide precursor solution is 1 mmol / mL to 2 mmol / mL.

[0017] In one embodiment, in the step S3, in the organic ammonium salt solution, the amount of FAI is 10 mg / mL to 100 mg / mL, and the amount of MACl is 5 mg / mL to 50 mg / mL.

[0018] In one embodiment, in step S2, the metal halide precursor solution further includes the second modifier; wherein the second modifier is perfluorooctyl quaternary ammonium iodide, and the amount of the perfluorooctyl quaternary ammonium iodide is 0.05 mg / mL to 0.2 mg / mL; or, the second modifier is potassium chloride, and the amount of potassium chloride is 0.6 mg / mL to 1.5 mg / mL.

[0019] In one embodiment, the step S2 includes the following steps: depositing the metal halide precursor solution on the surface of the electron transport layer obtained in the step S1 by spin coating, and annealing in a nitrogen atmosphere to form a metal halide layer; wherein the spin coating speed is 1200rpm~2000rpm, and the spin coating time is 25s~40s; and / or, during the annealing process, the annealing temperature is 70℃~90℃, and the annealing time is 1min~3min.

[0020] In one embodiment, the step S3 includes the following steps: depositing the organic ammonium salt solution on the surface of the metal halide layer obtained in the step S2 by spin coating, and annealing in an air atmosphere with a relative humidity of 30% to 40% to form a perovskite light-absorbing layer; wherein the spin coating speed is 1500rpm to 2500rpm, and the spin coating time is 25s to 40s; and / or, during the annealing process, the annealing temperature is 140°C to 180°C, and the annealing time is 12min to 18min.

[0021] In one embodiment, the method for preparing the perovskite solar cell comprises the following steps:

[0022] S1. Perform ultrasonic cleaning and UV-ozone treatment on the conductive substrate in sequence; prepare a SnO2 solution with a mass fraction of 3wt%; spin-coat the SnO2 solution on the surface of the conductive substrate at a spin-coating speed of 4000rpm for 30s; anneal at 150°C in a nitrogen atmosphere for 30min to form an electron transport layer;

[0023] S2, dissolving PbI2 and polyvinyl acetate in a solvent to obtain a metal halide precursor solution containing 1.5 mmol / mL of PbI2 and 0.6 mg / mL of polyvinyl acetate; spin coating the metal halide precursor solution on the surface of the electron transport layer prepared in step S1, with a spin coating speed of 1500 rpm and a spin coating time of 30 s; annealing at 70° C. in a nitrogen atmosphere for 1 min to form a metal halide layer;

[0024] S3, dissolving FAI and MACl in a solvent to obtain an organic ammonium salt solution containing 90 mg / mL FAI and 12 mg / mL MACl; spin coating the organic ammonium salt solution on the surface of the metal halide layer obtained in step S2, with a spin coating speed of 1800 rpm and a spin coating time of 30 s; annealing for 15 min in an air atmosphere at 150° C. and a relative humidity of 30%-40% to form a perovskite light absorbing layer;

[0025] S4. Prepare a PEAI solution containing 15 mmol / mL, and spin-coat the PEAI solution on the surface of the perovskite light-absorbing layer obtained in step S3 at a spin-coating speed of 4000 rpm for 30 seconds, and let it stand to form a passivation layer; and sequentially form a hole transport layer and a metal back electrode on the passivation layer to obtain the perovskite solar cell.

[0026] The technical solution of the present invention designs a two-step preparation process for a perovskite solar cell and a corresponding perovskite film, wherein a first modifier polyvinyl acetate is introduced into the lead iodide layer to delay the reaction of FAI and MACl in the lead iodide and organic ammonium salt layers, making the reaction slower and milder, thereby optimizing the nucleation and crystallization process of the perovskite film; the present invention also introduces a second modifier into the lead iodide layer and uses it in combination with the first modifier to act on the lead iodide layer, thereby further optimizing the reaction of the lead iodide layer and the organic ammonium salt layer; the present invention also reasonably controls the concentration and ratio of lead iodide, the modifier and the organic ammonium salt and matches the corresponding preparation process, thereby making the lead iodide residue in the prepared perovskite film smaller and having higher crystallinity and lower defect state density, thereby making the prepared perovskite solar cell have higher photoelectric conversion efficiency and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0028] Figure 1 This is a SEM electron microscope image of the perovskite light absorbing layer in the perovskite solar cell prepared in Comparative Example 1;

[0029] Figure 2 This is a SEM electron microscope image of the perovskite light absorbing layer in the perovskite solar cell prepared in Example 1;

[0030] Figure 3 The current density-voltage curves and corresponding device performance parameters of the perovskite solar cells prepared in Example 1 and Comparative Example 1;

[0031] Figure 4 The current density-voltage curve and corresponding device performance parameters of the perovskite solar cell prepared in Example 2;

[0032] Figure 5 The current density-voltage curve and corresponding device performance parameters of the perovskite solar cell prepared in Example 3;

[0033] Figure 6 The current density-voltage curve and corresponding device performance parameters of the perovskite solar cell prepared in Example 4;

[0034] Figure 7 is the current density-voltage curve and corresponding device performance parameters of the perovskite solar cell prepared in Example 5;

[0035] Figure 8 The current density-voltage curve and corresponding device performance parameters of the perovskite solar cell prepared in Comparative Example 2;

[0036] Fig. 9 The current density-voltage curve and corresponding device performance parameters of the perovskite solar cell prepared in Comparative Example 3;

[0037] Fig.10 It is a trend chart of the photoelectric conversion efficiency of the perovskite solar cells prepared in Example 1 and Comparative Example 1 as the use time increases under the same test conditions.

[0038] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, etc.), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components in a certain specific posture. If the specific posture changes, the directional indication will also change accordingly.

[0041] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features limited to "first" and "second" may explicitly or implicitly include at least one of the features. In addition, if "and / or" or "and / or" appears in the full text, its meaning includes three parallel solutions. Taking "A and / or B" as an example, it includes solution A, solution B, or solutions that satisfy both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0042] The technical problem solved by this application is: the two-step preparation process of perovskite film currently developed is to first deposit a layer of lead iodide, and then deposit an organic ammonium salt to react with lead iodide to finally form perovskite; compared with the one-step method, the prepared film has high density and is easy to prepare large-area perovskite film. However, the perovskite film prepared by the two-step method also has typical technical problems, such as insufficient reaction between organic ammonium salt and lead iodide, resulting in a large amount of lead iodide residue, which affects battery efficiency and battery stability.

[0043] It should be noted that in the related art, researchers in this industry will introduce solvents or small molecule additives that can form strong coordination with lead iodide into the lead iodide precursor solution to slow down the reaction rate of lead iodide and organic ammonium salts and promote their complete reaction, thereby optimizing the crystal growth of perovskite film. However, the above scheme is only effective in the short term, and neither solvents nor small molecule additives can have a long-term and stable passivation effect on perovskite films. Therefore, it is necessary to develop macromolecular polymer additives to achieve long-term delay of the reaction process of lead iodide and organic ammonium salts, thereby developing high crystalline quality, low defect state density and long-term stable perovskite films and perovskite solar cells.

[0044] In order to solve the above technical problems, the present application proposes a perovskite solar cell, wherein the perovskite solar cell includes a perovskite light absorbing layer, and the perovskite light absorbing layer includes a first modifier; the modifier includes polyvinyl acetate.

[0045] It should be noted that a two-step method is used in the present application to prepare the perovskite film, wherein the metal halide layer uses lead iodide, and the organic ammonium salt layer uses FAI and MACl. The main technical problem is that the reaction between lead iodide and the organic ammonium salt is too active, which, on the one hand, causes a large amount of lead iodide to remain in the perovskite film, and on the other hand, causes local oversaturation, and some crystals rapidly nucleate to form an uneven perovskite film. It will also cause an increase in structural defects such as grain boundaries and holes, reduce the film quality, and thus affect the photoelectric efficiency and stability of the perovskite film.

[0046] It should also be noted that in the present application, by adding polyvinyl acetate to the lead iodide precursor solution, a large amount of carbon-oxygen double bonds in polyvinyl acetate provide lone pairs of electrons as Lewis bases, competitively bind lead ions, reduce the contact efficiency of organic ammonium salts and lead iodide, thereby reducing the severity of the reaction of organic ammonium salts and lead iodide, making the nucleation and growth process of perovskite more controllable, avoiding the roughness of the film or holes caused by local rapid reactions, thereby promoting the complete reaction of lead iodide and organic ammonium salts and forming less lead iodide residues, and obtaining a higher quality perovskite film. The carbon-oxygen double bonds in polyvinyl acetate can also be combined with uncoordinated lead ions through coordination bonds, replace missing iodine ions, reduce the number of iodine vacancies, play a passivation role, reduce non-radiative recombination and reduce defect state density. In addition, polyvinyl acetate, as a high molecular polymer, can limit the excessively fast or disordered growth of perovskite crystals through larger steric hindrance, promote the orderly arrangement of perovskite grains, thereby obtaining a high crystallinity, dense, uniform perovskite film.

[0047] In one embodiment, the weight average molecular weight of the polyvinyl acetate is 20,000 to 100,000. Preferably, the weight average molecular weight of the polyvinyl acetate is 50,000. It should be noted that by limiting the parameters of the polyvinyl acetate within the above range, the crystal quality of the obtained perovskite film is higher and the defect state density is lower; thereby, the obtained solar cell has higher photoelectric conversion efficiency and stability.

[0048] In one embodiment, the perovskite light absorbing layer further includes a metal halide, and the metal halide includes lead iodide.

[0049] In one embodiment, the perovskite light absorbing layer further includes an organic ammonium salt, and the organic ammonium salt includes FAI and MACl.

[0050] It should be noted that the preparation method of the perovskite film in the present application is a two-step preparation process, including the preparation of a metal halide layer and the preparation of an organic ammonium salt layer. Wherein, the metal halide layer is obtained by depositing and annealing a metal halide, preferably, the metal halide is lead iodide; the organic ammonium salt layer is obtained by depositing and annealing an organic ammonium salt, preferably, the organic ammonium salt is a combination of FAI (formamidine hydroiodate) and MACl (methylammonium chloride). Further, the technical problems studied in this application include how to reduce the lead iodide residue in the process of forming perovskite crystals by reacting lead iodide with FAI and MACl.

[0051] In one embodiment, the perovskite light absorbing layer further includes a second modifier; the second modifier includes at least one of potassium chloride and perfluorooctyl quaternary ammonium iodide.

[0052] It should be noted that potassium chloride (KCl) as an inorganic passivating agent acts together with polyvinyl acetate in the perovskite formed by the reaction between lead iodide and FAI and MACl, which can reduce the non-radiative recombination of carriers by passivating the defect states such as cation vacancies and anion vacancies in the perovskite; in addition, potassium chloride as an ionic compound can also improve the interface contact between the perovskite light absorption layer and the electron transport layer or the hole transport layer. Perfluorooctyl trimethylammonium iodide as an organic small molecule passivating agent acts together with polyvinyl acetate in the perovskite formed by the reaction between lead iodide and FAI and MACl, which can passivate the defect states in the perovskite and reduce the non-radiative recombination of carriers; on the other hand, the molecular structure of perfluorooctyl trimethylammonium iodide can use its steric hindrance to slow down the reaction rate of lead iodide and organic ammonium salt, promote their complete reaction and reduce the lead iodide residue, so as to obtain a higher quality perovskite film.

[0053] It should also be noted that although inorganic passivators and organic small molecule passivators such as potassium chloride and perfluorooctyl quaternary ammonium iodide can also promote the delay of the intensity of the reaction between lead iodide and organic ammonium salt to a certain extent and promote complete reaction, inorganic passivators and organic small molecule passivators cannot achieve long-term and stable passivation effect; therefore, it is necessary to combine inorganic passivators and organic small molecule passivators such as potassium chloride and perfluorooctyl quaternary ammonium iodide with the first modifier polyvinyl acetate (high molecular polymer) in this application to act on the reaction between lead iodide and organic ammonium salt, so that the obtained perovskite film can have higher long-term stability.

[0054] The present application also proposes a method for preparing the perovskite solar cell, which comprises the following steps:

[0055] S1, forming a conductive substrate and an electron transport layer in sequence;

[0056] S2, dissolving a metal halide and a first modifier in a solvent to obtain a metal halide precursor solution; depositing the metal halide precursor solution on the surface of the electron transport layer obtained in step S1, and annealing to form a metal halide layer;

[0057] S3, dissolving an organic ammonium salt in a solvent to obtain an organic ammonium salt solution; depositing the organic ammonium salt solution on the surface of the metal halide layer obtained in step S2, and annealing to form a perovskite light-absorbing layer;

[0058] S4, forming a hole transport layer and a metal back electrode in sequence on the surface of the perovskite light-absorbing layer obtained in step S3 to obtain the perovskite solar cell.

[0059] It should be noted that in the preparation method of the perovskite solar cell of the present application, step S2 is the preparation of the metal halide layer, i.e., the lead iodide layer, and step S3 is to form an organic ammonium salt layer on the surface of the lead iodide layer and then react to obtain a perovskite light-absorbing layer. It should be further noted that the inventors have repeatedly studied and concluded during the research and development process that the performance of the perovskite battery prepared by adding the first modifier or the combination of the first modifier and the second modifier to the lead iodide precursor solution in step S2 is significantly better than the perovskite battery prepared by adding the organic ammonium salt precursor solution in step S3. This is because: adding the modifier or passivator first in the first step can preferentially interact with the cation vacancies and anion vacancies in the lead iodide layer, and regulate the microstructure and spatial uniformity of the lead iodide film; if the modifier or passivator is added in the second step, the lead iodide film has been formed at this time, and the defects are likely to exist and be fixed, resulting in the effect of the modifier or passivator being severely limited. Therefore, the introduction of modifiers or passivators in the first step can intervene in the crystallization process of perovskite and suppress defect formation, thereby more effectively reducing the defect density of perovskite films.

[0060] In one embodiment, in step S1, the electron transport layer is made of a SnO2 solution, and the mass fraction of SnO2 particles in the SnO2 solution is 3wt%. It should be noted that the material of the electron transport layer of the perovskite battery in the present application includes but is not limited to SnO2, and the mass fraction of the solute in the electron transport layer solution includes but is not limited to 3wt%.

[0061] In one embodiment, in step S2, the amount of the first modifier in the metal halide precursor solution is 0.1 mg / mL to 1 mg / mL. Preferably, the first modifier is polyvinyl acetate; preferably, the amount of the polyvinyl acetate is 0.6 mg / mL.

[0062] In one embodiment, in the step S2, in the metal halide precursor solution, the amount of the metal halide is 1 mmol / mL to 2 mmol / mL. Preferably, the metal halide is lead iodide; preferably, the amount of the lead iodide is 1.5 mmol / mL.

[0063] In one embodiment, in the step S3, in the organic ammonium salt solution, the amount of FAI is 10 mg / mL to 100 mg / mL, and the amount of MACl is 5 mg / mL to 50 mg / mL.

[0064] It should be noted that the inventors have concluded through long-term research that when the dosage of the first modifier polyvinyl acetate, the metal halide lead iodide and the combination of FAI and MACl in the organic ammonium salt respectively meets the above three ranges, the obtained perovskite film has a higher photoelectric conversion efficiency and better long-term stability.

[0065] In one embodiment, in step S2, the metal halide precursor solution also includes the second modifier; further, the second modifier is perfluorooctyl quaternary ammonium iodide, and the amount of the perfluorooctyl quaternary ammonium iodide is 0.05 mg / mL to 0.2 mg / mL; preferably, the amount of the perfluorooctyl quaternary ammonium iodide is 0.1 mg / mL.

[0066] In another embodiment, in step S2, the metal halide precursor solution further includes the second modifier; further, the second modifier is potassium chloride, and the amount of potassium chloride is 0.6 mg / mL to 1.5 mg / mL; preferably, the amount of potassium chloride is 1 mg / mL.

[0067] It should be noted that by compounding the first modifier and the second modifier and adding them to the lead iodide precursor solution in the first step of the two-step method, the first modifier can significantly improve the crystallization quality, and the second modifier has good defect passivation ability, which can achieve the technical effect of synergistically regulating the crystallization of the perovskite film and passivating the defect state of the perovskite film.

[0068] In one embodiment, the step S2 includes the following steps: depositing the metal halide precursor solution on the surface of the electron transport layer obtained in the step S1 by spin coating, and annealing in a nitrogen atmosphere to form a metal halide layer; wherein the spin coating speed is 1200rpm~2000rpm, and the spin coating time is 25s~40s; and / or, during the annealing process, the annealing temperature is 70℃~90℃, and the annealing time is 1min~3min.

[0069] In one embodiment, the step S3 includes the following steps: depositing the organic ammonium salt solution on the surface of the metal halide layer obtained in the step S2 by spin coating, and annealing in an air atmosphere with a relative humidity of 30% to 40% to form a perovskite light-absorbing layer; wherein the spin coating speed is 1500rpm to 2500rpm, and the spin coating time is 25s to 40s; and / or, during the annealing process, the annealing temperature is 140°C to 180°C, and the annealing time is 12min to 18min.

[0070] It should be noted that the annealing treatment of the lead iodide layer in step S2 needs to be carried out in a nitrogen atmosphere, while in step S3, the annealing treatment process of the organic ammonium salt layer needs to be annealed in an air atmosphere with a relative humidity of 30% to 40%. This is because: on the one hand, the presence of water molecules can reduce the activation energy of the reaction and promote the efficient reaction; on the other hand, under appropriate humidity conditions, water molecules can regulate the nucleation and growth process of perovskite crystals. If the environment is too dry, it will cause the perovskite crystals to nucleate too quickly, forming a large number of small grains, which are prone to introduce more defects. Of course, the air humidity should not be too high, otherwise it will cause too many water molecules to enter the perovskite crystals, causing them to decompose and affect the quality of the film. It should also be noted that after the lead iodide layer is formed in step S2, the operation in step S3 can only be performed after the lead iodide layer is naturally cooled to room temperature.

[0071] In one embodiment, the method for preparing the perovskite solar cell comprises the following steps:

[0072] S1. Perform ultrasonic cleaning and UV-ozone treatment on the conductive substrate in sequence; prepare a SnO2 solution with a mass fraction of 3wt%; spin-coat the SnO2 solution on the surface of the conductive substrate at a spin-coating speed of 4000rpm for 30s; anneal at 150°C in a nitrogen atmosphere for 30min to form an electron transport layer;

[0073] S2, dissolving PbI2 and polyvinyl acetate in a solvent to obtain a metal halide precursor solution containing 1.5 mmol / mL of PbI2 and 0.6 mg / mL of polyvinyl acetate; spin coating the metal halide precursor solution on the surface of the electron transport layer prepared in step S1, with a spin coating speed of 1500 rpm and a spin coating time of 30 s; annealing at 70° C. in a nitrogen atmosphere for 1 min to form a metal halide layer;

[0074] S3, dissolving FAI and MACl in a solvent to obtain an organic ammonium salt solution containing 90 mg / mL FAI and 12 mg / mL MACl; spin coating the organic ammonium salt solution on the surface of the metal halide layer obtained in step S2, with a spin coating speed of 1800 rpm and a spin coating time of 30 s; annealing for 15 min in an air atmosphere at 150° C. and a relative humidity of 30%-40% to form a perovskite light absorbing layer;

[0075] S4. Prepare a PEAI solution containing 15 mmol / mL, and spin-coat the PEAI solution on the surface of the perovskite light-absorbing layer obtained in step S3 at a spin-coating speed of 4000 rpm for 30 seconds, and let it stand to form a passivation layer; and sequentially form a hole transport layer and a metal back electrode on the passivation layer to obtain the perovskite solar cell.

[0076] The present invention is further described below by means of specific embodiments:

[0077] The raw materials used in the embodiments of the present invention are all commercially available, and the present invention does not impose any restrictions on the sources of the raw materials.

[0078] Example 1

[0079] The specifications of the raw materials used in Example 1 are as follows:

[0080] Polyvinyl acetate, CAS: 9003-20-7, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with a weight average molecular weight of about 50,000.

[0081] Perfluorooctyl quaternary ammonium iodide, CAS: 3486-22-7, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with the catalog number T836239.

[0082] Commercial SnO2 colloidal dispersion, mass fraction is 15wt%.

[0083] The method for preparing the perovskite solar cell in Example 1 comprises the following steps:

[0084] S1. Use deionized water, ethanol and isopropanol to clean the FTO conductive glass for 15 minutes respectively, dry it, and then treat it with UV-ozone for 15 minutes for standby use;

[0085] The commercial SnO2 colloidal dispersion and deionized water were diluted in a volume ratio of 1:4 to obtain a SnO2 solution. 50 μL of the solution was dropped on the surface of the FTO conductive glass and spin-coated at 4000 rpm for 30 seconds. The solution was then transferred to a 150°C hot stage and annealed for 30 minutes to obtain an electron transport layer.

[0086] S2, the electron transport layer prepared in the step S1 is subjected to UV-ozone treatment for 15 minutes for standby use; 1.5 mmol of lead iodide powder and 0.6 mg of PVAc are dissolved in a mixed solvent of 900 μL of DMF and 100 μL of DMSO to obtain a lead iodide precursor solution; 50 μL of the lead iodide precursor solution is dropped onto the surface of the electron transport layer prepared in the step S1 in a N2 glove box, and the mixture is spin-coated at a speed of 1500 rpm for 30 seconds, and then transferred to a 70°C hot stage for annealing for 1 minute to obtain a lead iodide layer;

[0087] S3, dissolving 90 mg of FAI and 12 mg of MACl in 1 mL of isopropanol to obtain an organic ammonium salt solution; dropping 100 μL of the organic ammonium salt solution on the surface of the lead iodide layer obtained in step S2, spin coating at a speed of 1800 rpm for 30 seconds, then transferring to air with a relative humidity of 30% to 40%, annealing on a hot stage at 150° C. for 15 minutes to obtain a perovskite light-absorbing layer;

[0088] S4, transferring the perovskite film obtained in step S3 to a nitrogen glove box, preparing a PEAI solution containing 15 mmol / mL, taking 50 μL of the PEAI solution and dropping it on the surface of the perovskite light-absorbing layer, spin coating at a speed of 4000 rpm for 30 seconds, and then standing in a nitrogen atmosphere for 10 minutes to obtain a passivation layer;

[0089] 72 mg of Spiro-OMeTAD was dissolved in 1 mL of chlorobenzene solution, 35 μL of 260 mg / mL acetonitrile solution of lithium bis(trifluoromethanesulfonyl)imide and 30 μL of 4-tert-butylpyridine were added, and the mixture was mixed to obtain a mixed solution; 50 μL of the mixed solution was dropped onto the surface of the passivation layer, and the mixture was spin-coated at a speed of 3000 rpm for 30 seconds, and then allowed to stand in a nitrogen atmosphere for 10 minutes to obtain a hole transport layer;

[0090] A 70nm thick gold electrode is formed on the surface of the hole transport layer by evaporation, the evaporation vacuum is controlled to be lower than 5×10-4Pa, and the deposition rate is 0.03nm / s; a perovskite solar cell is obtained.

[0091] Example 2

[0092] Example 2 is based on Example 1, except that in Example 2, in step S2, the concentration of PVAc in the lead iodide precursor solution is 0.1 mg / mL.

[0093] Example 3

[0094] Example 3 is based on Example 1, except that in Example 3, in step S2, the concentration of PVAc in the lead iodide precursor solution is 1 mg / mL.

[0095] Example 4

[0096] Example 4 is based on Example 1, except that: in Example 4, in step S2, 0.6 mg / mL of PVAc and 0.1 mg / mL of perfluorooctyl quaternary ammonium iodide are added to the lead iodide precursor solution.

[0097] Example 5

[0098] Example 5 is based on Example 1, except that in Example 5, in step S2, 0.6 mg / mL of PVAc and 1 mg / mL of potassium chloride are added to the lead iodide precursor solution.

[0099] Comparative Example 1

[0100] Comparative Example 1 is based on Example 1, except that: in Comparative Example 1, in step S2, PVAc is not added to the lead iodide precursor solution.

[0101] Comparative Example 2

[0102] Comparative Example 2 is based on Example 1, except that in Comparative Example 2, in step S2, the concentration of PVAc in the lead iodide precursor solution is 2 mg / mL.

[0103] Comparative Example 3

[0104] Comparative Example 3 is based on Example 1, except that: in Comparative Example 3, PVAc is not added to the lead iodide precursor solution in step S2 but is added to the organic ammonium salt solution in step S3.

[0105] Performance testing:

[0106] (1) The perovskite light absorbing layer prepared in step S3 of Example 1 and Comparative Example 1 was sampled and electron microscope images were taken, and the morphological characteristics of the grains were compared. Figure 1-2 ;

[0107] (2) The current density-voltage curves of the perovskite solar cells prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were measured respectively. Figure 3 to Figure 6 ; Figure 3 The curve of the target part corresponds to Example 1, and the curve of the control part corresponds to Example 1;

[0108] (3) The short-circuit current density (mAcm) of the perovskite solar cells prepared in Examples 1 to 3 and Comparative Examples 1 to 2 was respectively -2 ), open circuit voltage (V), fill factor (%) and photoelectric conversion efficiency (%) were measured. The measurement results are shown in Table 1.

[0109] Table 1

[0110]

[0111] By Figure 1 and Figure 2 By comparison, it can be seen that the grain size of the perovskite film prepared in Example 1 is significantly increased, and the white lead iodide phase is significantly reduced, and the crystallization quality of the perovskite film is significantly higher.

[0112] Through Fig.10 Analysis shows that, under the same test conditions, with the extension of the use time, the downward trend of the photoelectric conversion efficiency value of the perovskite battery in Example 1 is significantly weaker than that in Comparative Example 1. Therefore, the long-term stability of the perovskite battery in Example 1 is significantly higher than that in Comparative Example 1.

[0113] By analyzing Table 1, it can be seen that the perovskite battery prepared in Example 1 has a short-circuit current density (mAcm -2 ), open circuit voltage (V), fill factor (%) and photoelectric conversion efficiency (%).

[0114] Comparing Examples 4 to 5 with Example 1, it can be seen that the performance of the perovskite battery prepared by combining the first modifier and the second modifier is significantly improved.

[0115] Comparing Comparative Example 2 with Examples 1 to 3, it can be found that when an excessive amount of PVAc is added to the lead iodide precursor solution, the normal performance of the perovskite battery will be affected.

[0116] Comparing Comparative Example 3 with Example 1, it can be found that the performance of the perovskite solar cell obtained by performing the modification treatment in the second step of the two-step method is significantly weaker than that of the perovskite solar cell performed in the first step.

[0117] The above description is only an exemplary embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A perovskite solar cell, characterized in that: The perovskite solar cell includes a perovskite light absorbing layer, and the perovskite light absorbing layer includes a first modifier; The first modifier includes polyvinyl acetate.

2. The perovskite solar cell according to claim 1, characterized in that The weight average molecular weight of the polyvinyl acetate is 20,000 to 100,000.

3. The perovskite solar cell according to claim 1, characterized in that The perovskite light-absorbing layer further comprises a metal halide, and the metal halide comprises lead iodide; And / or, the perovskite light-absorbing layer further comprises an organic ammonium salt, and the organic ammonium salt comprises FAI and MACl.

4. The perovskite solar cell according to claim 1, characterized in that The perovskite light absorbing layer further includes a second modifier; The second modifier includes any one of potassium chloride and perfluorooctyl quaternary ammonium iodide.

5. A method for preparing a perovskite solar cell according to any one of claims 1 to 4, characterized in that: The method for preparing the perovskite solar cell comprises the following steps: S1, forming a conductive substrate and an electron transport layer in sequence; S2, dissolving a metal halide and a first modifier in a solvent to obtain a metal halide precursor solution; depositing the metal halide precursor solution on the surface of the electron transport layer obtained in step S1, and annealing to form a metal halide layer; S3, dissolving an organic ammonium salt in a solvent to obtain an organic ammonium salt solution; depositing the organic ammonium salt solution on the surface of the metal halide layer obtained in step S2, and annealing to form a perovskite light-absorbing layer; S4, forming a hole transport layer and a metal back electrode in sequence on the surface of the perovskite light-absorbing layer obtained in step S3 to obtain the perovskite solar cell.

6. The method for preparing a perovskite solar cell according to claim 5, characterized in that: In the step S1, the electron transport layer is prepared from a SnO2 solution, and the mass fraction of SnO2 particles in the SnO2 solution is 3wt%; And / or, in the step S2, the amount of the first modifier in the metal halide precursor solution is 0.1 mg / mL to 1 mg / mL; And / or, in the step S2, the amount of the metal halide in the metal halide precursor solution is 1 mmol / mL to 2 mmol / mL; And / or, in the step S3, in the organic ammonium salt solution, the amount of FAI is 10 mg / mL to 100 mg / mL, and the amount of MACl is 5 mg / mL to 50 mg / mL.

7. The method for preparing a perovskite solar cell according to claim 5, characterized in that: In the step S2, the metal halide precursor solution further includes the second modifier; Wherein, the second modifier is perfluorooctyl quaternary ammonium iodide, and the dosage of the perfluorooctyl quaternary ammonium iodide is 0.05 mg / mL to 0.2 mg / mL; or, the second modifier is potassium chloride, and the dosage of the potassium chloride is 0.6 mg / mL to 1.5 mg / mL.

8. The method for preparing a perovskite solar cell according to claim 5, characterized in that: The step S2 comprises the following steps: Depositing the metal halide precursor solution on the surface of the electron transport layer prepared in step S1 by spin coating, and annealing in a nitrogen atmosphere to form a metal halide layer; Wherein, the spin coating speed is 1200rpm-2000rpm, and the spin coating time is 25s-40s; and / or, during the annealing process, the annealing temperature is 70°C-90°C, and the annealing time is 1min-3min.

9. The method for preparing a perovskite solar cell according to claim 5, characterized in that: The step S3 comprises the following steps: Depositing the organic ammonium salt solution on the surface of the metal halide layer prepared in step S2 by spin coating, and annealing in an air atmosphere with a relative humidity of 30% to 40% to form a perovskite light-absorbing layer; Wherein, the spin coating speed is 1500rpm-2500rpm, and the spin coating time is 25s-40s; and / or, during the annealing process, the annealing temperature is 140°C-180°C, and the annealing time is 12min-18min.

10. The method for preparing a perovskite solar cell according to claim 5, characterized in that: The method for preparing the perovskite solar cell comprises the following steps: S1. Perform ultrasonic cleaning and UV-ozone treatment on the conductive substrate in sequence; prepare a SnO2 solution with a mass fraction of 3wt%; spin-coat the SnO2 solution on the surface of the conductive substrate at a spin-coating speed of 4000rpm for 30s; anneal at 150°C in a nitrogen atmosphere for 30min to form an electron transport layer; S2, dissolving PbI2 and polyvinyl acetate in a solvent to obtain a metal halide precursor solution containing 1.5 mmol / mL of PbI2 and 0.6 mg / mL of polyvinyl acetate; spin coating the metal halide precursor solution on the surface of the electron transport layer prepared in step S1, with a spin coating speed of 1500 rpm and a spin coating time of 30 s; annealing at 70° C. in a nitrogen atmosphere for 1 min to form a metal halide layer; S3, dissolving FAI and MACl in a solvent to obtain an organic ammonium salt solution containing 90 mg / mL FAI and 12 mg / mL MACl; spin coating the organic ammonium salt solution on the surface of the metal halide layer obtained in step S2, with a spin coating speed of 1800 rpm and a spin coating time of 30 s; annealing for 15 min in an air atmosphere at 150° C. and a relative humidity of 30%-40% to form a perovskite light absorbing layer; S4. Prepare a PEAI solution containing 15 mmol / mL, and spin-coat the PEAI solution on the surface of the perovskite light-absorbing layer obtained in step S3 at a spin-coating speed of 4000 rpm for 30 seconds, and let it stand to form a passivation layer; and sequentially form a hole transport layer and a metal back electrode on the passivation layer to obtain the perovskite solar cell.